Collaboration of Public Services of Phayao Elderly School, Nothern Thailand - PIYAKORN WHANGMAHAPORN (Jurnal Studi Pemerintahan, 2012)
This research project studies collaboration of public services of Phayao Elderly People in the northernpart of Thailand. The research questions are: ‘Which factors that make the collaboration possible?’,‘What are the processes of collaboration?’ and ‘What are the final results of the collaborations?’ Thisresearch aims to investigating the conditions leading into the collaboration of the school, examiningthe collaboration process and studying the results arising from the collaboration. This is a qualitativeresearch using the Phayao Elderly School as a case study. This school is the most successful elderlyschool in Thailand. Structured interviews and observations are used to understand the incidents as aframework for the interviews. Content analysis is also used to analyze recorded transcripts of theinterviews. The findings of this research are: 1) The factors which led to the formation of the elderlyschool are the deteriorations of the elderly people’s health, the increasing population of the elderlypeople, and the utilization of the elderly people’s free time after retirement to maintain and improvetheir lifestyles. 2) A network of collaboration to ensure the implementation of the elderly school and 3)The school can encourage the integrity and self-esteem of the elderly people. The number of students isincreasing every year. However, the funding for governmental collaboration has not increased.